Sub-MIC antibiotics increased the fitness cost of CRISPR-Cas in Acinetobacter baumannii - Yu, Ting; Huang, Jiayuan; Huang, Xinyue; Hao, Jingchen; Zhang, Pengyu; Guo, Tingting; Bao, Guangyu; Li, Guocai (Frontiers in Microbiology, 2024)
The escalating prevalence of bacterial resistance, particularly multidrug-resistant bacteria like Acinetobacter baumannii, has become a significant global public health concern. The CRISPR-Cas system, a crucial defense mechanism in bacteria against foreign genetic elements, provides a competitive advantage. Type I-Fb and Type I-Fa are two subtypes of CRISPR-Cas systems that were found in A. baumannii, and only the I-Fb CRISPR-Cas system regulates antibiotic resistance in A.baumannii. However, it is noteworthy that a majority of clinical isolates of A. baumannii lack or have incomplete CRISPR-Cas systems and most of them are multidrug-resistant. In light of this, our study aimed to examine the impact of antibiotic pressure on the fitness cost of the I-Fb CRISPR-Cas system in A. baumannii. Here, we conducted in vitro competition experiments to investigate the influence of sub-minimum inhibitory concentration conditions (sub-MIC) on the CRISPR-Cas systems' fitness cost in A. baumannii. We found that the fitness cost of the CRISPR-Cas system was increased under sub-MIC conditions. The expression of CRISPR-Cas-related genes was decreased, while the conjugation frequency was increased in AB43 under sub-MIC conditions. Through metabolomic analysis, we identified that sub-MIC conditions primarily affected energy metabolism pathways. In particular, we observed increased carbon metabolism, nitrogen metabolism, and intracellular ATP. Notably, the CRISPR-Cas system demonstrated resistance to the efflux pumpmediated resistance. Furthermore, the expression of efflux pump-related genes was increased under sub-MIC conditions. Our findings suggest that the I-Fb CRISPR-Cas system confers a significant competitive advantage in A. baumanni. However, under sub-MIC conditions, its function and the ability to inhibit the energy required for efflux pumps are reduced, resulting in an increased fitness cost and loss of competitive advantage.